SERVICE QUALITY DAN WORD OF MOUTH TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN BRIMO DI BANK RAKYAT INDONESIA KCP URIP SUMOHARJO SOLO - Ines Nur Isti Haryanti; Siti Maryam; Burhanudin Ahmad Yani (ITB AAS Indonesia Surakarta, 2020)
This study aims to determine partial and simultaneous Service Quality and Word Of Mouth on customer decisions to use Brimo at Bank Rakyat Indonesia KCP Urip Sumoharjo Solo. The population in this study were customers of Bank Rakyat Indonesia KCP Urip Sumoharjo Solo. The sampling technique uses the incidental random sampling method. Based on this method, a sample of 100 customers was obtained. The data analysis method used in this study is to use multiple linear regression analysis. Based on the results of simultaneous testing (F test), it shows that the independent variables ( Service Quality and Word Of Mouth) have a positive and significant effect on the dependent variable (customer decisions). Based on partial testing (t test), it shows that the variable Service Quality and Word Of Mouth have a positive and significant effect on customer decisions. Based on the test of the coefficient of determination (R2) obtained 44.3%, these results indicate that the dependent variable (Nasaban's decision) can be explained by independent variables ( Service Quality and Word Of Mouth), while the remaining 56.7% is influenced by variables outside of this study. Keywords: Service Quality , Word Of Mouth, Customer Decision, Brimo, BRI.